Spatially restricted coral bleaching as an ecological manifestation of within-colony heterogeneity - Christian R. Voolstra; Marlen Schlotheuber; Emma F. Camp; Matthew R. Nitschke; Sebastian Szereday; Sonia Bejarano (Communications Biology)
Abstract Coral bleaching is a widespread stress response of reef-building corals to elevated sea temperatures, resulting in the loss of symbiotic algae and often leading to coral death and reef degradation. Although coral bleaching occurs globally, not all reefs, species, colonies, or polyps bleach equally. Understanding intra-colony bleaching heterogeneity is crucial to anticipate the extent of coral loss at 2°C warming and harness variability to inform restorative interventions. Partially bleached coral colonies are commonly documented yet rarely tracked to determine whether they reflect ecologically distinct heterogeneity (e.g., in thermal tolerance) or eventually bleach completely. Focusing on bleaching that appears restricted to certain areas within a coral colony, we examine its putative basis in the spatial variability of the holobiont. A coral’s three-dimensional structure creates mosaics of microenvironments. Adaptations to these microenvironments are underpinned by intra-colony differences in Symbiodiniaceae association, microbiome assemblage, and nutritional status, giving rise to microhabitats. Genetic mosaicism and epigenetic changes further contribue to intra-colony phenotypic heterogeneity. We pinpoint methodologies to align spatially restricted bleaching to different forms of coral surface heterogeneity, examine the common assumption that coral fragments represent entire colonies, and illuminate implications for coral biology and restoration.